Women’s Experience of Telehealth Cancer Genetic Counseling - Zilliacus, E.; Meiser, B.; Lobb, Elizabeth; Kirk, J.; Warwick, L.; Tucker, K. (Springer, 2010)
Telegenetics offers an alternative model of delivering genetic counseling to rural and outreach areas; however there is a dearth of qualitative research into the patient’s experience. Twelve women who had received telemedicine genetic counseling for hereditary breast and/or ovarian cancer (HBOC) within the previous 12 months participated in a semi-structured telephone interview. The interview explored women’s experience with telegenetics, satisfaction, perceived advantages and disadvantages and quality of the interaction with their genetic professionals. Overall women were highly satisfied with telegenetics. Telegenetics offered them convenience and reduced travel and associated costs. The majority of women described feeling a high degree of social presence, or rapport, with the off-site genetic clinician. One woman with a recent cancer diagnosis, reported that telemedicine was unable to meet her needs for psychosocial support. This finding highlights the need to be mindful of the psychosocial support needs of women with a recent diagnosis being seen via telegenetics. Patients attending for HBOC genetic counseling are generally highly satisfied with the technology and the interaction. Care should be taken, however, with patients with more complex psychosocial needs.